Palcy Face: First remedy in Ecuador through microsurgery technique Viterbo (NTL). - Huaraca , Walter Francisco (Revista Universidad de Guayaquil, 2011)
Facial paralysis is a disfiguring disorder with significant emotional and psychological impact families, taking patients to the brink of suicide is a complex combination of axonal and muscle degeneration. In today’s technological advances, the best results are achieved in combination with microsurgery by facial nerve graft (Cross Face Nerv Graft) achieving a harmonious and symmetrical smile on their admissibility. Noteworthy that the microsurgical treatment of this disease were previously done in the United States, France, Brazil, Taiwan, Japan and now available in Ecuador.
Keywords: Palcy face; Bell´s palcy; End-to-side Neurorraphy; The Viterbo Techniques; Microsurgical free flap